Piaget and Parables Assimilated: A Response to Cole - Foster, James D. (Journal of psychology and theology, 1986)
Dick T. Cole's critique of our integration of Piagetian learning theory and Christ's parabolic method focuses on two primary concerns. The first concern is that the Bible should not be used as data, and the second that current psychological concepts cannot be meaningfully related to biblical times. In response to these concerns it is argued that the parables are recorded lessons and not theological concepts as Cole suggests, that the underlying structure of biblical lessons is relevant to modern learning theory, and that cultural specificity does not hinder the learning process but rather is an essential part of it.